AB1100 Patient self-management apps as one module of an integrated tight-control concept based on the examples of the digital applications rheumalive und axspalive. (15th June 2017) - Feuchtenberger, M; Kleinert, S; Schuch, F; Spähtling-Mestekemper, S; Kuhn, C; Welcker, M
Abstract : Background: Medical Applications have the potential to support physicians and patients to document the course of the disease and optimize therapies. We describe the linkage and integration of patient reported outcomes (PROs) into existing medical office software and rheumatologic documentation systems by means of the digital applications RheumaLive and AxSpALive. RheumaLive is certified as medical product class I, and certification for AxSpALive is in preparation. Methods: RheumaLive and AxSpALive are applications that can be downloaded free of charge from the common app-stores (Android, Apple) and installed on mobile devices (smartphones, tablets). A freeware version for PCs is also available (Windows- und Mac OS X-Version). A diary functionality allows to document the medication uptake (partially filed, memory-functionality for medication uptake available), validated scores like VAS, SJC, morning stiffness, FFBh (comparable to HAQ), BASDAI, RADAI, etc. and days of sick leave (+/- related to the rheumatic disease). All App-versions are password-protected, which is provided by the treating rheumatologist (relationship patient-physician). The patient reported outcomes are stored locally on the respective device. For the subsequent visit, they can be printed or sent encrypted to the treating physician via internet in a prespecified interval. A specific software allows to integrate the data into the existing medical office software. In daily practise, data entered by patients into RheumaLive can be screened and compared with collected clinical data and laboratory measures, because of it's certification as medical product. In case of an increasing disease activity the patient can be rapidly contacted and medication can be modified, if necessary. Regular F2F-appointments remain integral part of the medical care, even in case of good controlled disease activity. But in case of F2F-appointments, PROs can be delivered by patients, saving time and resources. The PROs can be made available to rheumatologic documentation systems like RheumaDok via predefined interfaces. Results: In a first pilot phase 54 patients in 4 rheumatologic specialised practices were documented. In the next phase the number of patients and participating practices/centres shall be increased. Further studies are necessary to show if the integration of PROs which are collected via electronical application can lead to an improvement of rheumatologic diseases. Conclusions: The integration of PROs collected with RheumaLive and AxSpALive into existing rheumalogic documentation systems allows a close monitoring of disease courses and therapies according to the "tight control" principle. Acknowledgements: RheumaLive and AxSpALive werde developed by Starhealth GmbH on behalf of UCB Pharma GmbH. Disclosure of Interest: M. Feuchtenberger Speakers bureau: UCB, S. Kleinert Speakers bureau: UCB, F. Schuch Speakers bureau: UCB, S. Spähtling-Mestekemper Speakers bureau: UCB, C. Kuhn: None declared, M. Welcker Speakers bureau: UCB